Local Wisdom Integration in Problem-Based Learning E-Modules: Impact on Science Literacy and Science Process Skills - Baiq Nabila Saufika Zainuri; Gunawan Gunawan; Kosim Kosim (Indonesian Publication Center, 2024)
The low levels of scientific literacy and science process skills among Indonesian students necessitate innovative approaches to learning. This study aimed to analyze the impact of using Problem-Based Learning (PBL) e-modules, incorporating local wisdom, on improving students' scientific literacy and science process skills. A systematic literature review (SLR) methodology was employed. Literature searches used relevant keywords in electronic databases such as Scopus, Web of Science, ERIC, and Google Scholar. The identified articles were screened based on inclusion and exclusion criteria, and their quality was assessed. Relevant data were extracted and analyzed both qualitatively and quantitatively. The study results indicate that PBL e-modules incorporating local wisdom effectively enhance students' scientific literacy and science process skills. Improvements were observed in concept understanding, critical thinking abilities, problem-solving skills, creativity, and learning motivation. Factors influencing the effectiveness of the e-modules include the quality of their design, the role of the teacher, and the learning context. This study recommends the broader development and implementation of such e-modules, teacher training in their use, and further research on the long-term impact of these modules on students' knowledge and skill retention.